Cross section of hadron production in yy collisions at LEP - Dova, María Teresa (1997)
The reaction e+e-→e+e-y*y*→e+e- hadrons is analysed using data collected by the L3 detector during the LEP runs at √s= 130-140 GeV and √s= 161 GeV. The cross sections σ(e+e-→e+e-hadrons) and σ(yy → hadrons) are measured in the interval 5 ≤ Wyy ≤ 75 GeV. The energy dependence of the σ(yy → hadrons) cross section is consistent with the universal Regge behaviour of total hadronic cross sections.